Study on oral smokeless tobacco use among migrant labourers and their attitude towards tobacco cessation in an urban settlement in Ernakulam district of Kerala - Anjana Rameshan; Leyanna Susan George; Devraj Ramakrishnan AND Anu Vasudevan (International Journal of Community Medicine and Public Health, 2019)
Background: Interstate migrant workers in the state of Kerala are increasing day by day. Tobacco usage is quite common among them; however, there are only few studies about oral smokeless tobacco consumption among them. The objectives of the study were to study the prevalence of oral smokeless tobacco use among migrant labourers in an urban settlement in Ernakulam district of Kerala and to assess the knowledge and attitude of users towards cessation. Methods: A cross sectional study was conducted among 140 migrant workers residing in an urban settlement in Kochi. Data regarding their socio demographic characteristics, knowledge, attitude and practices of smokeless tobacco consumption was collected using a questionnaire adapted from the global adult tobacco survey questionnaire (GATS). Data was entered into excel sheet and was analyzed using Epi Info. Results: The prevalence of oral smokeless tobacco was found to be 32.85%. Of which, majority of them used a tobacco-lime mixture called Khani (50%) and used tobacco on a daily basis (65.2%). It was observed that 71.74% of the users were unaware of the ill effects of the use of smokeless tobacco and 69.57% of them were not interested in quitting this habit. Among those who had quit, majority of them had done it on their will power alone. Conclusions: The use of smokeless tobacco is quite prevalent among the migrant population. Effective behavioural change communication activities need to be directed towards them